The girl who was supposed to die - Henry, April (Henry Holt and Company, 2013)
"She doesn't know who she is. She doesn't know where she is, or why. All she knows when she comes to in a ransacked cabin is that there are two men arguing over whether or not to kill her. And that she must run. Follow Cady and Ty (her accidental savior turned companion), as they race against the clock to stay alive"--